The effect of organic matter and thermal maturity on the wettability of supercritical CO2 on organic shales. (October 2017) - Guiltinan, Eric J.; Cardenas, M. Bayani; Bennett, Philip C.; Zhang, Tongwei; Espinoza, D. Nicolas
Highlights: Bulk wettability of an organic shale is shown to be water wet in the presence of dense supercritical CO2 . Increasing thermal maturity is found to have little to no effect on the bulk wettability. Increasing organic matter concentrations up to 7.9% is found to have no effect on bulk wettability. Abstract: The geologic sequestration of CO2 is a potential solution for decreasing anthropogenic atmospheric CO2 emissions by trapping it underground. A primary mechanism for storage is structural trapping where low permeability and high capillary entry pressure caprock materials hold back the buoyant CO2 from rising to the surface. The wettability (or contact angle) of reservoir and caprock materials in relation to CO2 and formation brine partly determines the efficiency of structural trapping. Current practice applies the results of individual reservoir-comprising minerals recorded under laboratory conditions, to rocks under in-situ reservoir conditions. However, the wide variety of measured contact angles reported in the literature calls this practice into question. Moreover, organic shales have not been the focus of systematic studies. Here we analyzed the wettability of CO2 on organic shales at various organic matter concentrations and thermal maturities. We found that bulk organic shale remains highly water wet with respect to CO2 despite changes to the maturity or concentration of organics. This finding is in contrast to recent molecular dynamic simulations and our initial expectations from previous pore-scale analyses in which organic matter was shown to be hydrophobic. The results are likely due to the remaining mineralogy of the rock dominating the wetting behavior despite concentrations of organics up to 7.9%. This means that reservoirs and aquifers capped by organic rich caprocks may be suitable locations for CO2 storage and that organic matter at concentrations below percolation threshold may not have a detrimental effect on structural trapping efficiency.